TEACHERS’ TECHNIQUES IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Agustin, Maulani (English Education Department of STKIP Pasundan, 2019)
This research aimed at investigating the techniques used by teacher in teaching English vocabulary of young learners as well as the reasons employing the techniques. Observations and interview were carried out to collect the data. The respondent of this research was the English teacher and the object is the process of technique in teaching English vocabulary. Based on the data collection, the researcher concluded that the techniques used by the English teacher were Spelling Rules and Keeping Record. The media used by the teacher was song. The reason why the teacher used those techniques were: (1) Help the students remember their vocabulary, (2) Attract the students’ attention to the lesson, (3) The techniques can be used in any situation.